Factorial Study to Evaluate the Individual and Combined Effects of b-Cyclodextrin and Sodium Lauryl Sulfate on the Solubility and Dissolution Rate of Etoricoxib - Chowdary1, K.P.R.; Namrata2, Nammi (Asian Journal of Chemistry, 2011)
The objective of the study is to evaluate the individual main effects and combined (or interaction) effects of b-cyclodextrin and sodium lauryl sulfate, a surfactant on the solubility and dissolution rate of etoricoxib in a series of 22 factorial experiments. The solubility of etoricoxib in purified water (1), water containing 5 mM of b-cyclodextrin (a), water containing 2 % sodium lauryl sulfate (b) and water containing 5 mM of b-cyclodextrin and 2 % sodium lauryl sulfate (ab) were determined as per 22 factorial design. The individual and combined effects of b-cyclodextrin and sodium lauryl sulfate in enhancing the solubility of etoricoxib were highly significant (p < 0.01). The solubility of etoricoxib was markedly enhanced by b-cyclodextrin (2.25 fold), sodium lauryl sulfate (32.16 fold) individually as well as combinedly by b-cyclodextrin and sodium lauryl sulfate (38.82 fold). Solid inclusion complexes of etoricoxib-b-cyclodextrin were prepared with and without sodium lauryl sulfate as per 22 factorial design by kneading method. The dissolution rate of etoricoxib from the b-cyclodextrin complexes prepared was studied in phosphate buffer of pH 7.4 (n = 4). The individual main effects of b-cyclodextrin and sodium lauryl sulfate in enhancing the dissolution rate (K1) and dissolution efficiency (DE30) were highly significant (p < 0.01). Whereas the combined effect of b-cyclodextrin and sodium lauryl sulfate in enhancing the K1 and DE30 was not significant (p > 0.05). A 2.90 and 3.15 fold increase in K1 and 4.09 and 2.91 fold increase in DE30 of etoricoxib was observed, respectively with b-cyclodextrin and sodium lauryl sulfate.